2013
DOI: 10.3390/molecules18032803
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Proanthocyanidins from Parkia biglobosa (Jacq.) G. Don. (Fabaceae) by Flow Injection Analysis — Electrospray Ionization Ion Trap Tandem Mass Spectrometry and Liquid Chromatography/Electrospray Ionization Mass Spectrometry

Abstract: Abstract:The present study investigates the chemical composition of the African plant Parkia biglobosa (Fabaceae) roots and barks by Liquid Chromatography -Electrospray Ionization and Direct Injection Tandem Mass Spectrometry analysis. Mass spectral data indicated that B-type oligomers are present, namely procyanidins and prodelphinidins, with their gallate and glucuronide derivatives, some of them in different isomeric forms. The analysis evidenced the presence of up to 40 proanthocyanidins, some of which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 46 publications
3
28
1
Order By: Relevance
“…Compound 1 was identified as hexahydroxydiphenoyl-glucose (HHDP-glucose), whose [M–H] - at m/z 481 fragmented to yield daughter ions at m/z 301 and 275. Compounds 2, 3, and 5 showed [M–H] - at m/z 783 and fragments at m/z 481, 301, and 275, which were identified as isomers of di-HHDP-glucose, also known as pedunculagin I ( Gordon et al, 2011 ; Santos et al, 2011 ; Tala et al, 2013 ). Compound 6 showed an [M–H] - at m/z 935, which yielded a fragment at m/z 633 due to the loss of one unit of ellagic acid ( m/z 301).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 1 was identified as hexahydroxydiphenoyl-glucose (HHDP-glucose), whose [M–H] - at m/z 481 fragmented to yield daughter ions at m/z 301 and 275. Compounds 2, 3, and 5 showed [M–H] - at m/z 783 and fragments at m/z 481, 301, and 275, which were identified as isomers of di-HHDP-glucose, also known as pedunculagin I ( Gordon et al, 2011 ; Santos et al, 2011 ; Tala et al, 2013 ). Compound 6 showed an [M–H] - at m/z 935, which yielded a fragment at m/z 633 due to the loss of one unit of ellagic acid ( m/z 301).…”
Section: Resultsmentioning
confidence: 99%
“…This compound was identified as di-HHDP-galloyl-glucose, also known as casuarinin ( Simirgiotis and Schmeda-Hirschmann, 2010 ; Fischer et al, 2011 ). Compound 4 , which presented [M–H] - at m/z 761 with fragments at m/z 635 and 609, was identified as ( epi ) gallocatechin-( epi )gallocatechin- O -gallate ( Tala et al, 2013 ). Compounds 7 , 8 , 9 , 10, and 12 were identified as galloyl monosaccharides, which resulted from esterification of glucose by 3–5 GA units (galloyl, m/z 170).…”
Section: Resultsmentioning
confidence: 99%
“…They displayed 2 amu difference from the corresponding B-type PACs at m/z 577, 865, 1153, 1441 and 1729 [5,7,24,31,35,36]. Further, the observed [M+H] + ions for A-type PAC dimers to hexamers at m/z 577*, 865*, 1153*, 1441* and 1729* also present 2 amu difference from the corresponding B-types at m/z 579*, 867*, 1155*, 1443* and 1731* [6,20,21] (Figure 1,2 and Table 2).…”
Section: The Observed [M-h]mentioning
confidence: 99%
“…These fragments can be found in our pseudospectra 4a–c. The recurrent neutral loss of 176 suggests that these compounds could be decorated with a glucuronide molecules as described by Tala et al 2013 (Gu et al 2003 ) and glycosides of A-type procyanidin have been previously found in cacao liquor (Hatano et al 2002 ). A scheme of the structures proposed is shown in Fig.…”
Section: Resultsmentioning
confidence: 73%